2022
DOI: 10.1002/app.52200
|View full text |Cite
|
Sign up to set email alerts
|

Remotely triggered curcumin release from stimuli‐responsive magneto‐polymericlayer‐by‐layerengineered nanoplatforms

Abstract: Curcumin is a promising natural drug in cancer therapy. However, its therapeutic applicability is limited by its low solubility, short half‐life, and low bioavailability. In this work curcumin is encapsulated in stimuli‐responsive magneto‐polymeric nanoplatforms aiming at improving its bioavailability and efficiency for delivery in biological media. MnFe2O4 magnetic nanoparticles (MNPs) were synthesized via thermal decomposition, coated with sodium citrate and then functionalized with multilayers of chitosan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The obtained NPs were coated with citrate molecules using a ligand exchange process. 45 For this, the precipitate was sonicated in a mixture of hexane and citric acid solution (100 mg/mL in DMSO) and the resulting NPs were centrifuged, washed with ethanol, and redispersed in ultrapure water at pH ∼7. The core−shell synthesis process was performed using a procedure analogous to that employed for synthesizing the core with the core itself serving as the seed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained NPs were coated with citrate molecules using a ligand exchange process. 45 For this, the precipitate was sonicated in a mixture of hexane and citric acid solution (100 mg/mL in DMSO) and the resulting NPs were centrifuged, washed with ethanol, and redispersed in ultrapure water at pH ∼7. The core−shell synthesis process was performed using a procedure analogous to that employed for synthesizing the core with the core itself serving as the seed.…”
Section: Discussionmentioning
confidence: 99%
“…The obtained NaYF 4 :NdYbHo­(7/15/3%) precipitate was collected by centrifugation and washed with cyclohexane. The obtained NPs were coated with citrate molecules using a ligand exchange process . For this, the precipitate was sonicated in a mixture of hexane and citric acid solution (100 mg/mL in DMSO) and the resulting NPs were centrifuged, washed with ethanol, and redispersed in ultrapure water at pH ∼7.…”
Section: Methodsmentioning
confidence: 99%
“…The GC model is particularly useful for predicting drug release profiles under different conditions [ 152 ]. Additionally, it can be adapted to describe dual-phased drug release [ 152 , 153 , 154 ]. The experimental data on the release of curcumin from MnFe 2 O 4 magnetic nanoparticles with multilayered CS–alginate (ALG) shells were a good fit to the GC model.…”
Section: Release Kinetics Mechanisms and Modelingmentioning
confidence: 99%
“…In recent decades, research on chemotherapy has demonstrated that most of anti‐cancer drugs can somewhat restrain tumor growth; however, due to some limitations such as premature degradation and incapability of discriminating between malignant and normal cells, they cause unwanted side effects and non‐specific cytotoxicity 1 . Targeted drug therapy systems, including nanomaterials, have been known as plausible solutions to cope with the issues 2–4 …”
Section: Introductionmentioning
confidence: 99%
“…1 Targeted drug therapy systems, including nanomaterials, have been known as plausible solutions to cope with the issues. [2][3][4] It has been asserted that nanomaterials are capable of being passively accumulated in tumors because of their higher permeability and retention (EPR). A nanoscale drug delivery system has diverse benefits, including but not confined to: (1) a targeted delivery that lowers systemic exposure to a potentially harmful compound while increasing drug concentration at the intended spot; (2) a steady rate of drug delivery to sustain a continuous treatment dose at the delivery site; and (3) improved drug stability as a result of protection against degradation and loss of drugs.…”
mentioning
confidence: 99%